Control of drill string torsional vibrations using optimal static output feedback. (January 2023) - Cruz Neto, H.J.; Trindade, M.A.
Abstract: Failures during oil extraction can have impacts on exploration costs and time, especially those caused by vibrations during the drilling phase. A proper way to reduce these detrimental failures is to design an active controller that efficiently mitigates vibrations with the constraint of using the limited amount of real time data available in field operations. In this context, a technique that might be suitable for the controller design is the optimal static output feedback (OSOF), that considers only the measured signals for feedback. Recently, the authors proposed some modifications to this technique, involving the addition of sensors locations and a new way of dealing with the dependence of the controller parameters on the system initial condition. The aim of this contribution is to apply this novel control technique to suppress drill string torsional vibrations and address all the particular aspects regarding the application of the proposed controller for the drill string problem, i.e., reformulation of the equations of motion as a stabilization problem, determination of the output matrix and linearization. Analyses and comparison of the proposed controller with proportional–integral (PI) and linear quadratic regulator (LQR) controllers are performed considering numerical simulations of a finite element model with a non-regularized dry friction function. Results indicate that the proposed controller has a performance similar to the LQR with a significantly reduced number of sensors, and also exhibits superior performance and robustness with an equivalent control effort over the PI controller. Highlights: Simulations with FEM and discontinuous friction for typical drilling conditions. Theoretical basis for application of OSOF control for nonlinear drilling system. Analyses showing proposed controller superiority over the one usually employed. Analyses showing controller robustness for large friction parameter variations.